Team approach to manage difficult-to-treat TB cases: Experiences in Europe and beyond - D’Ambrosio, L; Bothamley, G; Caminero Luna, J.A; Duarte, R; Guglielmetti, L; Muñoz Torrico, M; Payen, M.C; Saavedra Herrera, N; Salazar Lezama, M.A; Skrahina, A; Tadolini, M; Tiberi, S; et al. (Pulmonology, 2018)
AbstractAs recommended by the World Health Organization (WHO), optimal management of MDR-TB cases can be ensured by a multi-speciality consultation body known as ‘TB Consilium’. This body usually includes different medical specialities, competences and perspectives (e.g., clinical expertise both for adults and children; surgical, radiological and public health expertise; psychological background and nursing experience, among others), thus lowering the risk of making mistakes – or managing the patients inappropriately, in order to improve their clinical outcomes. At present, several high MDR-TB burden countries in the different WHO regions (and beyond) have introduced TB Consilium-like bodies at the national or subnational level to reach consensus on the best treatment approach for their patients affected by TB. In addition, in countries/settings where a formal system of consultation does not exist, specialized staff from MDR-TB reference centres or international organizations usually spend a considerable amount of their working time responding to phone or e-mail clinical queries on how to manage M/XDR-TB cases. The aim of this manuscript is to describe the different experiences with the TB Consilia both at the international level (European Respiratory Society – ERS/WHO TB Consilium) and in some of the countries where this experience operates successfully in Europe and beyond. The Consilium experiences are described around the following topics: (1) history, aims and focus; (2) management and funding; (3) technical functioning and structure; (4) results achieved. In addition a comparative analysis of the TB Consilia in the different countries has been performed.